Genome-wide marker discovery in three South African indigenous cattle breeds (Afrikaner Drakensberger and Nguni) using next generation sequencing - Van Marle-Koster, Este (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.